The Effect of Giving Sweet Orange Juice (Citrus sinensis) on The Fatigue Level of Football Athletes - Faqilah Fadiyah Fatah; Erni Rukmana; Esi Emilia; Hardi Firmansyah; Risti Rosmiati (Universitas Negeri Semarang, 2024)
Background: Football is a sport that combines aerobic and anaerobic endurance during training and matches. Physical fitness can support blood circulation function and heart work and increase muscle strength, speed, agility, and explosiveness. Muscle fatigue can be affected by various internal and external factors, including physiological, nutritional, exercise, psychological, environmental, and health factors. One of the nutritional factors that can affect muscle fatigue is micronutrients such as potassium. Potassium and vitamin C deficiency can lead to muscle weakness and fatigue. Objective: The purpose of this study is to determine the difference in the effect of giving isotonic drinks and sweet orange juice on the fatigue level of North Sumatra PPLP football athletes. Method: The research design is true experimental, with the post-test only with a control group design. The subjects consisted of 24 athletes who were selected using systematic random sampling. The level of fatigue is known through the RAST test. Bivariate analysis uses an independent sample t-test to determine the difference in influence between each variable. Results: As a result of this study, there was a significant difference in fatigue levels in the two groups. The average fatigue level value in the treatment group was 4.61±1.42, while the control group was 6.62±2.33 or the Sig. p<0.05 value was p = 0.01. Conclusion: This showed a significant difference in the mean level of athlete fatigue between the treatment group and the control group.